The separation of phytochemical compounds of spica prunellae and pericarpium of citrus reticula tae by using a reverse phase hplc method - Gan Chin, Chear (Universiti Sains Malaysia, 2009)
A reversed-phase HPLC-UV method was developed for the separation of phytochemicals in water, n-hexane, and methanol extracts of two of the very common used Chinese herbal medicine, Spica prunellae and pericarpium of Citrus reticulatae. The phytochemical components of these extracts were separated by RP-HPLC on a C-18 column and adjusting mobile phase (acetonitrile: methanol; 40: 60 v/ v), flow rate at 0.8 mL/min. The identification of phytochemicals separated by RP-HPLC with UV-detection at 280 nm and 320 nm is based on the comparison of peak retention times of some previously published works. However, this needs to be confirmed by the use of standard samples under the same experimental condition.